PENGEMBANGAN MEDIA PEMBELAJARAN SEJARAH LOKAL BERBASIS FILM DOKUMENTER MASYARAKAT MULTIKULTURAL UNTUK MENUMBUHKAN SIKAP TOLERANSI MAHASISWA DI STKIP-PGRI PONTIANAK - Agustian, Teguh; Sariyatun, S.; Musadad, Akhmad Arif (Sebelas Maret University (UNS), 2016)
The purpose of this research is the development of teaching media that can be realized in practice. In teaching and learning process, educators are obligated to develop teaching materials and supporting media as a learning tool. This is done in order to help learners to understand in receiving the lessons. As well as local history-based instructional media documentary film which is developed, by utilizing information technology, to facilitate educators deliver teaching materials and to help learners understanding the material which is received.The research method used is Research & Development (R & D) were adapted and modified by Borg & Gall. The step of the research include: (1) preliminary study (pro-survey), (2) development of the media, (3) Testing the effectiveness of the media. TestingÂ the effectiveness of the product is done by using experimental methods at STKIP-PGRI Pontianak, the researcher chose history education study program at the fifth the semester. The experimental study used two classes; those are A afternoon class as control group and B afternoon class as experimental group.The results obtained from the test of hypothesis of independent sample t test, p value = 0.020 (p <0.05) H0 is rejected, so there is a difference between the control and experimental class. It can be concluded that the history teaching medium with documentary films developed give significant influence on the studentâ€™ tolerance in the history study program at STKIP -PGRI Pontianak.